PARALINGUAL ELEMENTS IN EGYPTIAN PRINT COMMERCIAL ADVERTISEMENTS: A SEMIOTIC ANALYSIS - Mohammad Masrukhi (Arabic Literature Department, 2024)
Print media advertisements generally uses two displays, verbal displays accompanied by nonverbal. In nonverbal displays, it includes the use of paralingual elements. This study wants to reveal the meaning contained in nonverbal elements in commercial advertisements in Egyptian print media (Ikomcemes) in the form of paralingal. The goal is to find out the integration of the elements that form a complete discourse so that the meaning and message of the advertising discourse can be understood. This research data was collected from various newspapers, flayers, and magazines published in Egypt. Furthermore, the data is classified using the method of sorting the elements of the two elements as Leech's concept. The research findings are in the form of types of composition of elements that make up an advertising discourse, and then the findings are analyzed by utilizing the theory of discourse analysis and semiotics. The use of these two theories is not only to examine the meaning of the verbal text but also to examine simultaneously with the context that frames it. The results can be stated that although nonverbal elements do not have diverse patterns, their existence is very necessary to understand the message conveyed by advertisers, both verbal and noverbal.